Antimicrobial activities of biocompatible nanocapsules loaded with essential oils and their cyto/genotoxicity in human keratinocyte cell line - Kozics, K.; Kapustova, M.; Pangallo, D.; Annusova, A.; Geraci, C. (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
Essential oils (EOs) of Thymus capitatus (Th) and Origanum vulgare (Or) were encapsulated in biocompatible poly(ε-caprolactone) nanocapsules (NCs). These nanosystems exhibited antifungal, antibacterial and antibiofilm activities against Candida albicans, Staphylococcus aureus and Escherichia coli. Th-NCs and Or-NCs were more effective against all tested strains than pure EOs and at the same time were not cytotoxic on human keratinocyte cell line (HaCaT). The genotoxic effects of EO-NCs and EOs on HaCaT were evaluated using a comet assay for the first time, revealing that Th-NCs and Or-NCs did not induce DNA damage compared with untreated control HaCaT cells in vitro after 24 h. The cells morphological changes were assessed by label-free live cell Raman imaging. This study demonstrate the ability of poly(ε-caprolactone) nanocapsules loaded with thyme and oregano EOs to reduce microbial and biofilm growth and could be an ecological alternative in the development of new antimicrobial strategies. This work was supported by the VEGA Grant Agency of the Slovak Republic (grant No. 2/0055/20) and COST Action (CA17140), supported by COST (European Cooperation in Science and Technology).